The Effects Of Two Computerized Programs In Reducing Jordanian Tertiary Students' Spelling Errors - Rashed Al-Zuoud, Khalid Mahmoud (2014)
This study investigated the effects of using two computerized programs on reducing the spelling errors Jordanian tertiary students. Ginger and Microsoft Word 2007 were used as two modes of presentation. These programs represented the text-audio and text modes, respectively, according to the modality principle. The spelling error levels (i.e., high, medium, and low) of the students were compared. This study was conducted based on Mayer's cognitive theory of multimedia learning, dual route theory of efficient spelling, and spelling in the context approach. The modality principle was similarly used